Canine Mammary Tumors: A Review and Consensus of Standard Guidelines on Epithelial and Myoepithelial Phenotype Markers, HER2, and Hormone Receptor Assessment Using Immunohistochemistry. (January 2014) - Peña, L.; Gama, A.; Goldschmidt, M. H.; Abadie, J.; Benazzi, C.; Castagnaro, M.; Díez, L.; Gärtner, F.; Hellmén, E.; Kiupel, M.; Millán, Y.; Miller, M. A.; et al.
Although there have been several studies on the use of immunohistochemical biomarkers of canine mammary tumors (CMTs), the results are difficult to compare. This article provides guidelines on the most useful immunohistochemical markers to standardize their use and understand how outcomes are measured, thus ensuring reproducibility of results. We have reviewed the biomarkers of canine mammary epithelial and myoepithelial cells and identified those biomarkers that are most useful and those biomarkers for invasion and lymph node micrometastatic disease. A 10% threshold for positive reaction for most of these markers is recommended. Guidelines on immunolabeling for HER2, estrogen receptors (ERs), and progesterone receptors (PRs) are provided along with the specific recommendations for interpretation of the results for each of these biomarkers in CMTs. Only 3+ HER2-positive tumors should be considered positive, as found in human breast cancer. The lack of any known response to adjuvant endocrine therapy of ER- and PR-positive CMTs prevents the use of the biological positive/negative threshold used in human breast cancer. Immunohistochemistry results of ER and PR in CMTs should be reported as the sum of the percentage of positive cells and the intensity of immunolabeling (Allred score). Incorporation of these recommendations in future studies, either prospective or retrospective, will provide a mechanism for the direct comparison of studies and will help to determine whether these biomarkers have prognostic significance. Finally, these biomarkers may ascertain the most appropriate treatment(s) for canine malignant mammary neoplasms.